2001
DOI: 10.3109/10428190109097748
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Splenectomy for Patients with Mantle Cell Non-Hodgkin's Lymphoma

Abstract: The purpose of this study was to define the role of splenectomy in patients (pts) with mantle cell lymphoma (MCL) with regard to improving cytopenias and symptoms of splenomegaly. 26 pts with MCL underwent splenectomy between January 1987 and October 1999 and were followed prospectively for hematologic response and operative morbidity and mortality. A positive response was defined at 1 month of follow-up as: a hemoglobin of > or = 1.0 g/dl in a pt with a preoperative value < 11.0 g/dl; or a platelet count of >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
1
4
0
5
Order By: Relevance
“…A high proportion of MCL and CLL patients (used as a comparative group) with cytopenias showed an improved haemoglobin and platelet count after splenectomy similar to the rates previously reported (Delpero et al, 1987;Gallhofer et al, 1987;Stein et al, 1987;Thiruvengadam et al, 1990;Majumdar & Singh, 1992;Neal et al, 1992;Coad et al, 1993;Pegourie-Bandelier et al, 1995;Cusack et al, 1997;Yoong et al, 2001). A difference was seen in the response of the leucocytosis in MCL, where the leucocyte count showed a downward trend after splenecctomy, in some cases persisting for long periods.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…A high proportion of MCL and CLL patients (used as a comparative group) with cytopenias showed an improved haemoglobin and platelet count after splenectomy similar to the rates previously reported (Delpero et al, 1987;Gallhofer et al, 1987;Stein et al, 1987;Thiruvengadam et al, 1990;Majumdar & Singh, 1992;Neal et al, 1992;Coad et al, 1993;Pegourie-Bandelier et al, 1995;Cusack et al, 1997;Yoong et al, 2001). A difference was seen in the response of the leucocytosis in MCL, where the leucocyte count showed a downward trend after splenecctomy, in some cases persisting for long periods.…”
Section: Discussionsupporting
confidence: 83%
“…Despite this, half of the patients with MCL and leukaemia had prolonged treatment-free periods after splenectomy. Yoong et al (2001) reported similar results in their patients with MCL; four out of 26 patients did not require further therapy post splenectomy, with a mean follow up of 95AE4 months, and eight additional patients did not require therapy for over a year, with a median time to treatment of 28 months.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Спленектомія не розглядається як лікувальна опція у рекомендаціях ESMO з лікування MCL [2,11]. Проте в літературі є повідомлення про добрі безпосередні та віддалені результати спленектомії при MCL [7,8,12]. Такі повідомлення поодинокі, а кількість прооперованих хворих не надто велика, що зумовлено насамперед низькою частотою цієї лімфоми.…”
Section: результатиunclassified